Foreword - Aydın, Orhan; Özen, Ali; Köse, Ercan; Çiçek, Serdar; Biçer, Mustafa Berkan; Alcan, Veysel; Özkazanç, Yakup (Institute of Electrical and Electronics Engineers Inc., 2024)
[Abstract Not Available]
32nd IEEE Conference on Signal Processing and Communications Applications, SIU 2024 -- 15 May 2024 through 18 May 2024 -- Mersin -- 201235